Gentrification, residential ethnicization and the social production of fragmented space in two multi-ethnic neighbourhoods of Lisbon and Bilbao - Malheiros, Jorge (2013)
Simultaneous trends for ethnicization and gentrification are contributing to the fragmentation of contemporary urban spaces. This is characterised by the emergence of new social and urban units that break the homogeneity of the modern city and lead to the development of new networks, territorially discontinuous, less neighbourhood centred and with a limited intersection. With Mouraria (Lisbon, Portugal) and San Francisco (Bilbao, Spain), two traditional and multiethnic neighbourhoods, as case-studies this paper aims to critically discuss the nature of gentrification, its coexistence with ethnicization and its contribution for socio-urban fragmentation. The empirical analysis of the residents’ social networks will be used to test levels and types of interaction and the spatial formats they assume.